PENGARUH AUDIT TENURE, UKURAN PERUSAHAAN, DAN UKURAN KAP TERHADAP AUDIT REPORT LAG DENGAN SPESIALISASI AUDITOR SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (2015-2021) - Anwar, Chairul -; Nurlaila, Nurlaila; Hasugian, Hotbin (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this research aimed to anlyzed the effect of Audit Tenure, Company Size, and KAP Size on Audit Report Lag with Auditor Specialization as Moderating Variable. This research used secondary data, that were from audited financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2021 period. The study population was 181 manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2021 period. Sample selected by purposive sampling, amount of 99 companies with 5 years of observation were 495 datas. The analysis method used was Logistic Regression Analysis and Moderated Regression Analysis (MRA). Based on the results of this research showed that audit tenure and company size don't significantly influence audit report lag, KAP size significantly influence audit report lag.Auditor specialization doesn’t moderate the relationship of audit tenure and company size to audit report lag. However, auditor specialization does moderate the relationship of KAP size on audit report lag in manufacturing companies listed in Indonesia Stok Exhange in year of 2015-2021.